'Sustainable Development': the 'Unsustainable' Development of a Concept in Political Discourse. (26th September 2012) - Kambites, Carol Jill
ABSTRACT This article uses critical discourse analysis to analyse national level discourses of sustainable development in the UK through the 1990s and 2000s, as revealed in five documents produced by successive national governments during this period. After briefly reviewing the concept of sustainable development and its interpretations, national sustainable development discourses are analysed in the context of the wider political discourses that have arisen around the political ideologies of neo‐liberalism, Thatcherism and New Labour. A critical discourse analysis, using the concept of 'discursive techniques', reveals the way in which the concept of sustainable development has been adapted to conform to the dominant political discourses of neo‐liberalism, Thatcherism and New Labour. In this process, the term has been used to emphasize the compatibility of economic growth and environmental protection, and hence, arguably, has been used to avoid rather than to facilitate radical action. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.